PENGARUH KECERDASAN EMOSIONAL DAN KREATIVITAS TERHADAP PRESTASI KERJA KARYAWAN PRODUKSI PADA PT. MULER PASIFIC LABELINDO, JAWA BARAT - Aris Budiono (LPPM Universitas Asa Indonesia, 2018)
Purpose- This study aims to determine the effect of Emotional Intelligence and Creativity on Work Achievement of production employees of PT Labelindo PT. Pacifik Design/methology/approach- The author conducted a survey by distributing questionnaires to 21 respondents in this study for testing and using saturated samples. To examine the effect of Emotional Intelligence and Creativity on Work Performance, the authors use multiple linear regression analysis with F test and t test. Findings- The value of t counts on the variable emotional intelligence (X1) with sign = 0.473. By using a degree of confidence (α = 5%), then partially the emotional intelligence variable (X1) has no significant effect, as much as the variable creativity (X2) with sig. = 0,000. By using the degree of confidence (α = 5%), then partially the creativity variable (X2) has a significant effect on the variable employee employment production of PT.Muler Pasific Labelindo. Simultaneously these two variables together affect employee performance. With the t-test, it was found that Emotional Intelligence has a significant impact on increasing employee motivation. The correlation coefficient value is 0.788, meaning that there is a strong and unidirectional relationship between the independent variables and the dependent variable. While the coefficient of determination (R²) is 0.621 Research limitations- The contribution of the independent variable consisting of emotional intelligence (X1) and creativity (X2) to the work performance of the production employees of PT.Muler Pasific Labelindo is 62.1%, while the remaining 37.9 % is influenced by other variables not included in the model or not examined